Truck Loading Dock Process – Investigating Integration of Sustainability - Niels Hackius; Wolfgang Kersten (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Truck loading docks as a bottleneck and a logistics interface notoriously plagued with misunderstandings and scheduling issues recently came to the attention of research in the wake of the 2011 report of the German federal office for goods transport. At the truck loading dock the different objectives of road haulers and warehouse operators collide having implications for the whole supply chain. This study aims to verify problems identified in earlier studies with a special focus on SME and explore the question how practitioners would include sustainability measures in that process. A qualitative interview method was used for the investigation, including various players from the logistics industry. A focus group discussion as well as nine face-to-face semi-structured interviews were used to gather optimization and sustainability integration suggestions for the loading dock processes. An increased need for information, a primary focus on efficiency as a method to become more sustainable, especially ecological sustainability as well as a lack of consideration of social issues were found. The research is limited due to the small sample that naturally cannot take all perspectives into account. The perspective of truck drivers is not included. Practitioners are to gather new ideas for the sustainability concepts as well as optimization methods for the loading dock processes in their enterprises; a long term outcome of this research project will be a best-practice catalogue.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; transport; loading docks; logistic interfaces; sustainable process improvements